Analizing labour supply of elderly people. A life-cycle approach - de Hek, Paul; van Erp, Frank (The Hague, 2009)
"In light of the ageing of the Dutch society, policy measures aim at increasing the participation rate of elderly workers, particularly in the age-group between 55 and 64. This paper develops a stylized numerical simulation model describing consumption, savings and labour supply behaviour over the life cycle to analyze the labour-market implications of such proposals. For example, we simulate a shift in the (normal) retirement age from 65 to 67, the elimination of the Social Security premium exemption after age 65, and a premium on first-tier pension benefits if the commencement date of these benefits is postponed. Each of these reforms affect the economic outcomes via wealth effects, income effects and inter- and intratemporal substitution effects. The stylized model offers a profound theoretical underpinning which helps us to understand these policy effects over the entire life cycle of individuals. However, the numerical outcomes should be taken with some caution as the model ignores insights of behavioural economics (such as ‘framing effects’)."